1998
DOI: 10.1292/jvms.60.985
|View full text |Cite
|
Sign up to set email alerts
|

Presence of 22 and 17-kDa Proteins Reacting with Sera in Mice Experimentally Infected with Brachyspira (Serpulina) hyodysenteriae.

Abstract: ABSTRACT. The antibodies to B. (S.)hyodysenteriae in experimentally infected mice were detected by microscopic agglutination test (MAT) and enzyme-linked immunosorbent assay (ELISA). The reactions in MAT were serotype specific while those in ELISA were common to both strains. A further investigation with immunoblotting technique demonstrated that 22-and 17-kDa proteins reacted strongly with the sera. The proteins in ATCC 27164 strain strongly reacted with the serum from ATCC 31212 strain-infected mouse and vic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…These results demonstrated that the antibodies may induce an antibacterial mechanism in vivo which could lead to the protection of pigs from swine dysentery. On the other hand, we have carried out studies with experimental infection of mice with B. hyodysenteriae which had been treated with SP and reported the presence of 22‐ and 17‐kDa proteins which reacted strongly with the sera from mice infected with B. hyodysenteriae [11]. The proteins in strain ATCC 27164 strongly reacted with the serum from mice infected with strain ATCC 31212 and vice versa.…”
Section: Introductionsupporting
confidence: 82%
“…These results demonstrated that the antibodies may induce an antibacterial mechanism in vivo which could lead to the protection of pigs from swine dysentery. On the other hand, we have carried out studies with experimental infection of mice with B. hyodysenteriae which had been treated with SP and reported the presence of 22‐ and 17‐kDa proteins which reacted strongly with the sera from mice infected with B. hyodysenteriae [11]. The proteins in strain ATCC 27164 strongly reacted with the serum from mice infected with strain ATCC 31212 and vice versa.…”
Section: Introductionsupporting
confidence: 82%